THE PROFILE OF CREATIVE THINKING PROCESS: PROSPECTIVE MATHEMATICS TEACHERS - Gunawan, Gunawan; Ferdianto, Ferry; Mulyatna, Fauzi; Untarti, Reni (Universitas Labuhanbatu, 2025)
Purpose The creative thinking process is one of the important components of creativity. The profile of the creative thinking process of prospective mathematics teachers based on the level of creativity is explained in this study.Methodology –The applied research method was qualitative with an exploratory approach. The research involved 35 prospective mathematics teachers in the Multivariable Calculus course. The data collection techniques were creative thinking tests and interviews. Data analysis uses data reduction techniques, presentation, and conclusion drawn.Findings –The stages of the creative thinking process include preparation, incubation, estimation, illumination, and verification stages. The study results show that the profile of the creative thinking process of students in the creative and creative category can find unique ideas, and their application is carried out in detail. Each stage of creative thinking is fulfilled clearly. Especially for the estimation stage, it is a new finding in the creative thinking process. The estimation stage makes a real contribution to the birth of creativity. The term to describe the estimation stage is